PERLINDUNGAN HUKUM BAGI PEKERJA/BURUH YANG MENGALAMI KECELAKAAN KERJA BERDASARKAN PP NOMOR 44 TAHUN 2015 TENTANG PENYELENGGARAAN PROGRAM JAMINAN KECELAKAAN KERJA DAN JAMINAN KEMATIAN - NANDA PRAMAS CAHYA; H. Zaeni Asyhadie (Private Law, 2023)
This study intends to comprehend the implementation of legal protection for workers who suffer job-related accidents during their employment and to identify the factors that become a barrier to the company within their effort in executing the work accident insurance. The research methodology used is normative-empirical legal research, which makes use of several approaches such as statute approach, conceptual approach, and sociological approach. The data sources include primary and secondary data along with the use of primary, secondary, and tertiary legal materials. The data collection techniques involve literature review and field data collection, followed by descriptive-qualitative analysis. The research findings indicate that the implementation of legal protection for workers who experience work accidents in PT. Narmada Awet Muda has been partially carried out; however, there are some obstacles, such as delays in the process of claiming work accident insurance benefits. Another contributing factor is the lack of labor supervision personnel in the Department of Labor and Transmigration.